Post-Financial Close Management Of Public-Private Partnership And Build-Operate-Transfer Contracts In Supporting The Achievement Of Sustainable Development Goals - Fauzee; Mohd Sofian Omar; I.R. Maruf (Magister Kenotariatan Universitas Pasundan, 2026)
Public-Private Partnership (PPP) and Build-Operate-Transfer (BOT) schemes have been positioned by the United Nations as strategic instruments to achieve the Sustainable Development Goals (SDGs), particularly SDG 9 on Industry, Innovation and Infrastructure, SDG 11 on Sustainable Cities and Communities, SDG 16 on Peace, Justice and Strong Institutions, and SDG 17 on Partnerships for the Goals. Indonesia faces an infrastructure investment need of IDR 10,303 trillion for the 2025-2029 period, making PPP and BOT schemes vital instruments. However, the success of long-term infrastructure projects is not only determined by initial planning and financing but is also highly dependent on contract management after financial close. This article analyzes global best practices in PPP and BOT contract management based on a study of more than 250 infrastructure projects and 25 case studies from various countries, integrating the People-First PPP paradigm developed by UNECE as a bridge between contract management and SDG achievement. The research employs a qualitative method with normative and comparative approaches, supported by semi-structured interviews with three officials and PPP project consultants. The results indicate that 45 percent of global PPP contracts undergo renegotiation before their tenth year, while Indonesia still faces challenges in dual land rights, the absence of professional contract management units, and the weak integration of SDG indicators in post-contract performance evaluation. By reviewing the Indonesian legal framework and comparing it with international practices in Colombia, South Africa, and the United Kingdom, this article formulates five SDG-based strategic recommendations to strengthen the governance of partnership-based infrastructure projects.